Hot forging behaviour of medium carbon and microalloyed steel: a comparative study. (2017) - Equbal, Md Israr; Ohdar, Rajkumar; Talukdar, Pinaki; Mukerjee, Debasis
The present work aims at studying and comparing the effect of forging variables on mechanical properties of two grades of steel, namely, medium carbon steel and medium carbon steel micro-alloyed with vanadium. Forging was done in flat dies of 150 ton hydraulic press at a temperature of 1000 ± 50°C followed by cooling in normal air, forced air and quenching oil mediums. Microstructures and mechanical properties were evaluated by optical microscopy, charpy impact, vickers hardness, yield and tensile tests before and after forging up to 40% reduction. Comparison of results shows that micro-alloyed steels had higher strength and hardness than medium carbon steel for all cooling conditions. Oil quenching leads to the formation of relatively fine ferrite and pearlite in the medium carbon steel whereas, martensite, bainite with precipitation of vanadium carbides and carbonitrides were present in the matrix of ferrite-pearlite in microalloyed steel.